An Exploratory Analysis of Individual Information Processing - Cravens, David W. (Management Science, 1970)
Information-processing is an integral part of decision-making; yet the state of knowledge concerning the individual problem solver in his role as an information-processor is limited. This paper presents a conceptual framework for examining individual, task-oriented information-processing as a multi-stage process. Relationships between variables in the model are investigated at a research site which provides a number of the advantages of both a laboratory and a field environment. The “information element” is used as the basic unit of analysis. Data are examined via the multivariate statistical technique of canonical analysis. The implications of the study are also discussed.